2011
DOI: 10.1007/s00280-011-1693-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketoconazole-mediated CYP3A4 inhibition on clinical pharmacokinetics of panobinostat (LBH589), an orally active histone deacetylase inhibitor

Abstract: PurposePanobinostat is partly metabolized by CYP3A4 in vitro. This study evaluated the effect of a potent CYP3A inhibitor, ketoconazole, on the pharmacokinetics and safety of panobinostat.MethodsPatients received a single panobinostat oral dose on day 1, followed by 4 days wash-out period. On days 5–9, ketoconazole was administered. On day 8, a single panobinostat dose was co-administered with ketoconazole. Panobinostat was administered as single agent three times a week on day 15 and onward.ResultsIn the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…After 4 weeks of persisting grade 4 leukopenia, POS treatment was stopped as presumed culprit and leukopenia improved. This interaction could have been predicted based on the interaction of panobinostat with ketoconazole where panobinostat maximum serum concentrations were increased by an average of 1.6‐fold …”
Section: Discussionmentioning
confidence: 99%
“…After 4 weeks of persisting grade 4 leukopenia, POS treatment was stopped as presumed culprit and leukopenia improved. This interaction could have been predicted based on the interaction of panobinostat with ketoconazole where panobinostat maximum serum concentrations were increased by an average of 1.6‐fold …”
Section: Discussionmentioning
confidence: 99%
“…However, as CYP3A4 is also a major liver enzyme catalyzing drug metabolism, there is a major concern that ritonavir may increase the serum concentration of panobinostat excessively and cause severe adverse events. However, a clinical study using panobinostat with ketoconazole as a CYP3A4 inhibitor, demonstrated that the combination increased the maximum concentration (Cmax) of panobinostat 1.6-fold and the area under the curve 1.8-fold, without significantly altering the time required to reach Cmax or the half-life (6). The authors of that study concluded that co-administration of panobinostat with CYP3A inhibitors is feasible, as the increases in the parameters of panobinostat pharmacokinetics were not clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for quantitation and pharmacokinetic analysis of erlotinib (24, 25) and panobinostat (26) have been previously published. The disposition of erlotinib in the presence of panobinostat (days 9 and 15) was compared to that shown in the absence of panobinostat (day 8).…”
Section: Methodsmentioning
confidence: 99%